2019
DOI: 10.1002/cctc.201801963
|View full text |Cite
|
Sign up to set email alerts
|

Modified Graphene Oxide Based Zinc Composite: an Efficient Catalyst for N‐formylation and Carbamate Formation Reactions Through CO2 Fixation

Abstract: Catalytic fixation of CO2 through chemical reactions is always a challenging task of synthetic chemistry. This paper represents the design and synthesis of an eco‐friendly low cost zinc metal containing heterogeneous catalyst of aminically modified Graphene Oxide. Characterization of the catalyst has been carried out by Raman and FTIR spectra, AAS, XRD, TEM, SEM, EDX and N2 adsorption desorption studies. It was found that the catalyst was very proficient for the CO2 fixation through N‐formylation and carbamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 131 publications
0
16
0
Order By: Relevance
“…The lower angled peak is obtained due to (002) plane whereas higher angled peak is for (100) plane of carbon hexagonal structure in graphene oxide. [61] The d-spacing value (i. e. interlayer spacing) of GO is 0.89 nm. [62] Raman spectroscopy mainly figured out the molecular inelastic (Raman) scattering based information when a molecule is irradiated with a monochromatic light such as laser.…”
Section: Characterization Of Carbocatalyst Graphene Oxide (Go)mentioning
confidence: 99%
“…The lower angled peak is obtained due to (002) plane whereas higher angled peak is for (100) plane of carbon hexagonal structure in graphene oxide. [61] The d-spacing value (i. e. interlayer spacing) of GO is 0.89 nm. [62] Raman spectroscopy mainly figured out the molecular inelastic (Raman) scattering based information when a molecule is irradiated with a monochromatic light such as laser.…”
Section: Characterization Of Carbocatalyst Graphene Oxide (Go)mentioning
confidence: 99%
“…Khatun et al [124] reported zinc metal containing aminically modified GO catalyzed CO 2 fixation through N-formylation and carbamate formation reactions of amines. It was found that N-formylation of both aromatic and aliphatic amines gave high yield of the corresponding formylated products in the presence of polymethylhydrosiloxane as reducing agent under 1 bar CO 2 pressure and mild temperature.…”
Section: Metal Oxide Nps Supported On Go/rgo Catalyzed Organic Transfmentioning
confidence: 99%
“…as well as heterogeneous catalysts like nitrogen-based polymers, ionic liquids, metal-organic frameworks (MOFs), porous-organic polymers (POPs), ion-exchange resins, metal oxides, supported metal catalysts, and more have been reported for the conversion of epoxides into cyclic carbonates utilizing CO 2 . [16][17][18][19][20][21][22][23][24][25][26][27][28] In particular, heterogeneous, porous nanocatalysts are advantageous due to their easy separation, good recyclability and large surface area. 29 Furthermore, it could be more sustainable if catalysts can be designed using abundant and non-toxic material resources for cyclic carbonate formation under mild conditions.…”
Section: Introductionmentioning
confidence: 99%